(untitled) (Bangladesh Journal of Neurosurgery, 2022)
Collection of proper autopsy specimen and preservation are essential stepsfor the toxicological analysis in Forensic Medicine. Faulty collection and preservation of the specimens/samples can greatly alter or negate forensic chemical or toxicologicalexamination. In forensic toxicology practicein Bangladesh, postmortem specimen that is subjected to toxicological examinations generally focusing on mainly blood and sometimes urine or other fuds from different body cavities. Analysis of blood from different anatomical sites and tissue samples and urine may assist in the interpretation of the postmortem results. However, in many postmortem cases, there is little or no blood for quantitative drug analysis, or there might be such traumatic injury which led to significant blood loss or there is possibility of contamination form contents of the ruptured stomach. Besides, analysis of urine reveals negative result, if death occurs closely the time of intoxication. Given the circumstances, brain tissue may be a valuable specimen in postmortem toxicological analysis. The position of the brain in the body secures a tremendous protection and isolation which can eliminates or at least attenuates many of the interpretive challenges with postmortem blood, urine or other fluid specimens.This review paper is an update on the standard methods of brain tissue specimen collection and preservationprocedures for toxicological analysis and its value as well as advantages over other specimens, which might be of possible interest for forensic professionals in the country. Bang. J Neurosurgery 2022; 11(2): 114-117